The Idea of Solidarity in the Concept of a Human Being Created in God's Image = Notion de solidarité dans la conception de l’être humain créé à l’image de Dieu = L’idea di solidarietà nel concetto di uomo creato a immagine di Dio - Petro, Marek (Philosophy & canon law, 2022)
Moral theology concerns the morality of society and acts of an individual or a group of individuals that constitute that particular society. Morality teaches us to properly respond to God’s calling, so that we can fulfil our ultimate goal. The Catechism of the Catholic Church, regarded as a compendium of the doctrines of the magisterium of the Church, can also serve as a valuable source for teaching moral theology. In the first section ("Man’s Vocation Life in the Spirit") of the third part ("Life in Christ") of the Catechism of the Catholic Church, we can learn that man has been created "in the image and likeness of the Creator" (chap. 1, art. 1), where solidarity plays a significant role. The present paper analyses this issue.